Essential oils of Baccharis trinervis (Asteraceae) from Costa Rica - Chaverri, Carlos (2017)
Baccharis is an Asteraceae genus of flowering plants, which has about 340 to 400 species, ranging from the Southern United States to the Southern extreme of Argentina and Chile through Central America and the Caribbean regions. The species Baccharis trinervis is a native shrub from Mexico, Central America and throughout South America. In Costa Rica, this species is commonly known as alcotán and the fresh leaves are used as a poultice on wounds and ulcers. The objective of the present research was to characterize the chemical composition of seven hydrodistilled essential oils of diverse morphological parts of B. trinervis. For this, samples were obtained from three locations in Costa Rica and standard laboratory analyses were followed. The essential oils were analyzed by capillary gas chromatography-flame ionization detector (GC-FID) and gas chromatography-mass spectrometry (GC-MS) using the retention indices on a 5 % phenyl/dimethylpolysiloxane fused silica column in addition to mass spectral fragmentation patterns, which allowed the identification of 268 compounds. The essential oils consisted mainly of terpenoids (92.3 to 97.8 %). The major constituents from the leaf oils were caryophyllene oxide (0.1-22.5 %), viridiflorol (8.8-21.0 %), germacrene D (0.5-19.1 %), germacrene B (0.2-16.0 %), β-caryophyllene (3.5-9.1 %), spathulenol (0.1-8.3 %), δ-3-carene (2.0-6.8 %), and α-pinene (2.5-5.9 %). The flower oil consisted mainly of globulol (0-24 %), β-caryophyllene (9.5-17.1 %), cis-muurola-4(14), 5-diene (traces-13.7 %), germacrene D (4.3-9.9 %), bicyclogermacrene (5.9-8.3 %), ar-curcumene (0-8.0 %), spathulenol (4.3-4.8 %), caryophyllene oxide (3.1-4.7 %), and viridiflorol (0.3-4.7 %). The major components of the branch oil were germacrene B (1.4-18.7 %), germacrene D (14.7-15.6 %), β-caryophyllene (10.1-12.4 %), viridiflorol (0-11.5 %), globulol (0.6-11.3 %), δ-3-carene (4.1-8.1 %), β-phellandrene (1.5-6.5 %), and bicyclogermacrene (3.6-4.9 %). The essential oil composition differed markedly from that of previously studied oils of plants growing in Brazil, which contain two characteristic stereoisomeric methyl dec-2-en-4,6-diynoate compounds not detected in this study. This is the first report about the chemical composition of the essential oils obtained from this species growing wild in Costa Rica.